2023
DOI: 10.3389/fcvm.2023.1189884
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of blood urea nitrogen in heart failure: a systematic review and meta-analysis

Siyu Duan,
Yuqi Li,
Ping Yang

Abstract: BackgroundThe mortality rate of patients with heart failure (HF) remains high, and when heart failure occurs, blood urea nitrogen (BUN) is involved in the perfusion of renal blood flow. Some studies have shown an association between heart failure prognosis and blood urea nitrogen, but the results of some other studies were inconsistent. Therefore, we conducted a comprehensive meta-analysis to investigate the value of BUN on the prognosis of patients with heart failure.MethodsA computerized systematic search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…And the predictive value of BUN for heart failure remains controversial in the literature. Sachdeva et al 33 found that BUN did not have any predictive value for heart failure prognosis, while Takaya et al reported that BUN was predictive only when combined with renal failure. Therefore, further exploration is necessary to determine whether BUN affects the prognosis of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…And the predictive value of BUN for heart failure remains controversial in the literature. Sachdeva et al 33 found that BUN did not have any predictive value for heart failure prognosis, while Takaya et al reported that BUN was predictive only when combined with renal failure. Therefore, further exploration is necessary to determine whether BUN affects the prognosis of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, little is known about the importance of BUN or the BUN/creatinine ratio in the chronic setting where major changes in volume status, and associated peaks of neurohumoral activation, over short periods are less common. 3,8 We have investigated whether the BUN/creatinine ratio has the same independent prognostic value in ambulatory patients and whether this differs between those with HFrEF and HF with preserved ejection fraction (HFpEF) using data from five large randomized trials.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in the acute setting, dehydration, and hypovolaemia, as well as other problems such as upper gastrointestinal bleeding, may lead to greater increases in BUN, relative to creatinine, and in patients hospitalized with worsening HF, elevated BUN and BUN/creatinine ratio is associated with worse outcomes, independently of eGFR or creatinine alone 5–7 . However, little is known about the importance of BUN or the BUN/creatinine ratio in the chronic setting where major changes in volume status, and associated peaks of neurohumoral activation, over short periods are less common 3,8 . We have investigated whether the BUN/creatinine ratio has the same independent prognostic value in ambulatory patients and whether this differs between those with HFrEF and HF with preserved ejection fraction (HFpEF) using data from five large randomized trials.…”
Section: Introductionmentioning
confidence: 99%
“…However, blood urea nitrogen (BUN) and serum creatinine (SCr) are not very accurate and specific markers of kidney function in acute coronary syndrome [11]. For instance, the BUN and SCr are not accurate renal function indexes due to the abnormal BUN/SCr ratio observed in patients with heart failure [12]. The levels of the serum biomarkers mentioned above and urine biomarkers among patients with liver failure were affected by numerous factors, including ingestion of creatinine, excretion of drugs, protein intake, sex, and age [13].…”
Section: Introductionmentioning
confidence: 99%